Ease of use and Usefulness Evaluation of Medical Family Tree Data Visualization - Fatimah Bokhare, Siti; Mohd Nazmee Wan Zainon, Wan; Azam Osman, Mohd; Zawawi Talib, Abdullah (International Journal of Engineering and Technology, 2018)
Ease of use and usefulness are two of the evaluation methods that are used frequently to evaluate software or visualization tools. It is used to investigate user acceptance and usually requires a model explaining people's attitudes and behavior as well as reliable and valid measurement instruments. Family trees on the other hand have many potentials to be explored for research purposes, especially medical family tree data or genogram. However, some limitations exist while using family tree or genogram, namely problems in visualizing the wealth and complexity of the information represented once a family tree gets bigger and more complex. Hence, a framework for exploring medical family tree data is proposed. This paper focus on the evaluation part that has been done in order to evaluate the ease of use and usefulness of the proposed visualization framework. The results will be helpful in understanding the potential and limitations of the proposed approach.Â